Glutamate-Mediated Primary Somatosensory Cortex Excitability Correlated with Circulating Copper and Ceruloplasmin - Franca Tecchio (International Journal of Alzheimer's Disease, 2011)
Objective. To verify whether markers of metal homeostasis are related to a magnetoencephalographic index representative of glutamate-mediated excitability of the primary somatosensory cortex. The index is identified as the source strength of the earliest component (M20) of the somatosensory magnetic fields (SEFs) evoked by right median nerve stimulation at wrist. Method. Thirty healthy right-handed subjects (51±22 years) were enrolled in the study. A source reconstruction algorithm was applied to assess the amount of synchronously activated neurons subtending the M20 and the following SEF component (M30), which is generated by two independent contributions of gabaergic and glutamatergic transmission. Serum copper, ceruloplasmin, iron, transferrin, transferrin saturation, and zinc levels were measured. Results. Total copper and ceruloplasmin negatively correlated with the M20 source strength. Conclusion. This pilot study suggests that higher level of body copper reserve, as marked by ceruloplasmin variations, parallels lower cortical glutamatergic responsiveness.